Kids COVID-19, Course, and Prevention - Samina Khan Bashir; Muhammad Bashir Khan (Hail Journal of Health Sciences, 2023)
The novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has influenced human beings globally; it was first discovered in Wuhan, China, in December 2019. It presents a broad spectrum of clinical signs and symptoms in different age groups with different outcomes. Various research has been going on to control the viral pandemic. Like adults, this novel virus has affected the population of children. However, the course of COVID-19 in children is different from adults. This review article will discuss the SARS-CoV-2 course, diagnosis, management, and prevention in children.